Exploring knowledge sharing and hiding on employees' creative behaviors: A coopetition perspective - Ge Yao; Zhao Hong; Yimei Hu; Xuejiao Zheng (Journal of Innovation & Knowledge (JIK), 2023)
Employees are encouraged to share their knowledge to stimulate creativity and innovation. However, individuals may hide their knowledge to pursue personal interests. Drawing on the coopetition perspective, this study investigates how individual-level knowledge sharing and hiding behaviors jointly influence employees' creative behaviors, as well as the knowledge sharing-hiding interaction mechanisms. We adopt a mixed-method design combining qualitative and quantitative analyses. Two types of knowledge sharing are identified: Proactive and reactive, both of which promote employees' creative behaviors. A follow-up empirical test shows that knowledge-hiding behaviors positively moderate the relationship between reactive knowledge sharing and employees' creative behaviors. However, knowledge-hiding behaviors demonstrate an inverted U-shaped moderating effect on the relationship between proactive knowledge sharing and employees' creative behaviors. This study makes a pioneering attempt to study the interplay between knowledge sharing and knowledge hiding and challenges the conventional notion regarding the role of knowledge hiding in employees' creative behaviors.
Keywords: L20; M10; M20; 650; Knowledge sharing; Knowledge hiding; Employees' creative behaviors; Coopetition; Service digitization